(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2022)
Users can access their data in today’s reporting environment, but it does not address all of their issues. The people have access to the statistics, but they cannot ensure the data’s truthfulness or the speed with which it is returned. Data warehousing addresses the aforementioned issues by providing technology that allows users or decision makers to analyze large amounts of data in a short period of time. Data warehousing allows users to extract information in real time, which assists them in making decisions. Many businesses wish to utilize the information for additional reasons. As a result, methods for mining fresh information from data warehouses have developed. Data collection and data excavation provide the groundwork for developing choice provision and decision making information system tools that track an organization’s progress concerning its objectives. Data mining and warehousing are technologies that allow a user in the business sector or government to analyze large amounts of data and make choices that benefit the whole organization. This article uses appropriate graphics to explain the impression, benefits, and drawbacks of data mining and warehousing. The duties and responsibilities of data warehousing organizational members are also addressed in this article. To sum up, we’re attempting to demonstrate how “Data Mining (DM) & Date Warehouses (DW)" may be utilized in companies, how data can aid making decisions, and how managers can conduct extra precise, meaningful, and consistent analysis using their data.